PRODUCTIVITY MEASUREMENT OF MALAYSIAN GOVERNMENT HOSPITALS USING DATA ENVELOPMENT ANALYSIS - Razli Che Razak (Asian Academy of Management Journal, 2003)
Traditionally, productivity is defined in terms of the efficiency of transforming inputs into outputs. However, researchers have always argued that the concept of productivity should not be limited to efficiency only, ignoring the phenomenon of effectiveness. This is particularly true in an organization that is not profit-oriented, such as non-governmental and governmental organizations, where efficiency may take a back seat as opposed to effectiveness. This paper takes the approach of measuring productivity by incorporating both efficiency and effectiveness, when measuring the productivity of public hospitals in Malaysia. However, given the different unit of measures as well as the differences in the nature of the data measuring efficiency and effectiveness, we needed a method that was able to combine both subjective as well as objective data. Thus, we found the Data Envelopment Analysis (DEA) most useful for a composite measure of productivity. The main findings show that productivity measures using both efficiency and effectiveness through the DEA is more meaningful than a measure with efficiency only. The effectiveness variable is found to have an impact on measuring productivity.